2022
DOI: 10.3389/feart.2022.800924
|View full text |Cite
|
Sign up to set email alerts
|

3D Visualization Monitoring and Early Warning System of a Tailings Dam—Gold Copper Mine Tailings Dam in Zijinshan, Fujian, China

Abstract: A 3D tailings dam visualization early warning system was developed based on GIS (geographic information system) combining ARIMA (autoregressive integrated moving average model) and 3S (RS, GIS, GPS) technology for prediction of phreatic line changes and tailing dam deformation. It was applied for monitoring and early warning for the gold–copper tailing dam in Zijinshan Dadongbei tailing pond. The system consists of equipment management, data management, prediction, monitoring and early warning, and 3D visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated the great impacts of tailings on environmental quality and the ecological landscape (Nie et al, 2022). For example, affected by Hg mining deposits, the average contents of Hg and Ni in agricultural soil in Gongguan of Shaanxi province exceeded the national secondary standard value by 3.9, and 4.0 times, respectively (Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have demonstrated the great impacts of tailings on environmental quality and the ecological landscape (Nie et al, 2022). For example, affected by Hg mining deposits, the average contents of Hg and Ni in agricultural soil in Gongguan of Shaanxi province exceeded the national secondary standard value by 3.9, and 4.0 times, respectively (Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Significant progress has been made in domestic and international research on 3S technology in the field of mine monitoring, yielding important results. Wen Nie et al [6] carry out the design and research of tailing dam monitoring and early warning system based on computer, cloud computing, GIS, and time series prediction technology. 3D geographic information system can manage multisource data effectively and realize two-and three-dimensional visual displays.…”
Section: Introductionmentioning
confidence: 99%
“…3S technology has made notable advancements in addressing issues related to limited data visualization, suboptimal data management, and the feasibility of point-surface combination prediction and early warning systems. Through the application of this technology, highprecision prediction of mine safety risks and real-time disaster early warning can be achieved [6] . This paper summarizes the characteristics and advantages of 3S technology, builds upon previous researchers' approaches, and proposes four suggestions for improvement, with the aim of establishing an efficient, accurate, and secure monitoring system to enhance the overall efficiency of mining area monitoring projects.…”
Section: Introductionmentioning
confidence: 99%
“…The tailings dam is generally designed as a permeable structure, and the saturation line of dam is called lifeline. Safety evaluation based on monitoring data of rainfall, saturation line, water level and deformation of tailings dam is a common means to solve safety early warning problems (Wang et al, 2018), and the monitoring system of tailings dam is becoming more and more perfect (Nie et al, 2022). The depth of saturation line is the direct external response to the change of seepage field of tailings dam.…”
Section: Introductionmentioning
confidence: 99%